Economic and employment impacts of offshore wind for Ireland: A value chain analysis. Issue 11 (1st September 2020) - Kandrot, Sarah; Cummins, Val; Jordan, Declan; Murphy, Jimmy
ABSTRACT: The imminent development of a number of offshore wind farms in the Republic of Ireland presents a sizable opportunity to stimulate the Irish economy through the growth of an indigenous and globally competitive offshore wind supply chain. This study uses a value chain analysis to evaluate the economic and employment potential of the offshore wind sector for Ireland. The analysis is based on the expenditure on products and services required to develop an offshore wind farm, the planned capacity of projects in the pipeline, and the ability of Irish companies to supply the sector. Results suggest that by 2030, 2.5–4.5GW of domestic offshore wind development could create between 11, 424 and 20, 563 supply chain jobs and generate between €763 m and €1.4bn in gross value added. This is the first study to estimate domestic GVA potential for the sector.